Formulation and Evaluation of Natural Gel Containing Ethanolic Extract of Pandanus amaryllifolius R. Using Various Gelling Agents - Dyera Forestryana; Annisa Hayati; Aristha Novyra Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Ethanol extract of Pandanus amaryllifolius leaves contains quercetin has anti-inflammatory properties. The gel dosage form is very appropriate for wound healing therapy because it gives a cold sensation to the skin. This study aims to formulate a P. amaryllifolius gel by variation of a gelling agent to compare the effect of a natural gelling agent, semi-synthetic gelling agent, and synthetic gelling agent on the physical characteristics of the gel. The gel formulation was made in three formulas. Evaluations include organoleptic, homogeneity, spreadability, adhesion, pH, and viscosity. The optimum gel formula was tested for release study using a dissolution apparatus 5. Determination of release kinetics model using the kinetics approach of zero-order, first-order, Higuchi, and Korsmeyer-Peppas. The organoleptic shows the gel's dark green color, P. amaryllifolius aromas, and good homogeneity. The gel formulas had pH values that matched the physical quality criteria of the gel. Data obtained for the spreadability test for F1, F2, and F3 were 12.16, 14.66, and 10.75 g.cm/sec, respectively. The F1, F2, and F3 adhesion test results were 11.66, 10, and 47.33, respectively. The viscosity of F1 was 15750 cps, F2 was 4807 cps, and F3 was 19380 cps. This study concludes that the optimum formula is obtained from the gelling agent of Na-CMC as a gelling agent. The number of quercetins released from F2 was 42.76%, and the release kinetics model followed the kinetics of Higuchi.